428 Accomplishing Realignment Goals Withstands the Test of Time: The Outcomes of a Prospective Consecutively Enrolled Single-Center Adult Cervical Deformity Series With Minimum 5-Year Follow-Up. (April 2023) - Passias, Peter G.; Williamson, Tyler K.; Joujon-Roche, Rachel; Imbo, Bailey; Krol, Oscar; Tretiakov, Peter S.; Bennett-Caso, Claudia; Owusu-Sarpong, Stephane; Lebovic, Jordan
Abstract : INTRODUCTION: Adult cervical deformity(CD) realignment has shown promising short-term and two-year clinical results, but longer-term outcomes of CD surgery remain unclear. METHODS: Operative CD patients>18 years eligible for 5-year (5Y) follow-up were included. Optimal thresholds for C2 Slope and T1 Slope by Passfall et al were assessed. Student's t-test, paired t-test, binary and multivariable logistic regression analyses were used to evaluate the clinical, radiographic, and complications outcomes of the five-year eligible cohort. RESULTS: 58 patients were enrolled from 2012 to 2017(54.5±10.3 years, 57% female, BMI: 30.0 ± 7.3 kg/m 2, 16% osteoporosis), and underwent surgical correction (levels fused: 5.2 ± 2.6, EBL: 772 ± 672 mL, operative time: 372 ± 139 min, LOS: 5.9 ± 8.1 days). By surgical approach, 13.8% anterior-only, 51.7% posterior-only, 34.5% combined. 53% had previous cervical surgery, 41% a fusion. The most common UIV was C3, LIV was T1. By three months (3M), patients improved in cervical lordosis, C2-C7 SVA (cSVA), and T1 Slope(all p <.02), but not C2 Slope or TS-CL (both p>.5). The cohort significantly improved from baseline (BL) to 2Y in NDI, NRS-Neck, and EQ-5D(all P<.02). From 2Y to last follow-up, patients did not improve in mJOA or NDI, but did in EQ-5D (0.441 to 0.509) and NRS-Neck (5.9 to 5.0, both p<.05). There were 14(24.1%) cases of DJK, 6 were distal junctional failure (10.3%), and 17(29.3%) underwent reoperation. Patients corrected below the T1 Slope threshold of 26.5° and maintained at last follow-up experienced DJK less often(OR: 0.1, [0.02-0.74]). Patients corrected below the C2 Slope threshold of 10° and maintained at last follow-up experienced no DJK, DJF or reoperations. CONCLUSIONS: Although complications including distal junctional failure and reoperation remain prevalent, correction of cervical deformity and achievement of realignment targets results in notable clinical and radiographic improvement with most patients achieving favorable outcomes by two years, with further improvement seen until last follow-up.